Age and tumor size as independent predictors of malignancy in BI-RADS 4 and 5 breast lesions: A cross-sectional study in Vietnam - De Van Nguyen; Trung Van Pham; Tam Huu Dinh; Dung Ngoc Tran; Chung Thanh Dang (PLoS ONE, 2026)
Background Accurate diagnosis of suspicious breast lesions (BI-RADS 4/5) is crucial for appropriate clinical management. The International Academy of Cytology (IAC) Yokohama System standardizes fine-needle aspiration (FNA) cytology reporting, but its performance and the role of independent clinical predictors within this specific high-risk cohort require further investigation. This study aimed to evaluate the diagnostic performance of FNA using the Yokohama system and to identify independent predictors of malignancy in patients with BI-RADS 4 and 5 lesions. Methods and findings We conducted a cross-sectional study of 104 female patients with BI-RADS 4/5 breast lesions at two tertiary hospitals in Vietnam. All patients underwent ultrasound-guided FNA with subsequent histopathological examination as the gold standard. Diagnostic performance metrics were calculated. Univariate and multivariate logistic regression analyses were performed to identify independent predictors of malignancy. Of the 104 lesions, 53 (51.0%) were confirmed to be malignant. FNA cytology, interpreted with the Yokohama System, demonstrated a sensitivity of 92.5%, specificity of 96.1%, and an overall accuracy of 94.2%. In the multivariate analysis, only two factors emerged as strong, independent predictors of malignancy: older age (adjusted odds ratio [aOR] 1.13 per year, 95% CI: 1.07–1.19; p < 0.001) and larger tumor size (aOR 1.10 per mm, 95% CI: 1.04–1.16; p = 0.001). Notably, the predictive value of a BI-RADS 5 classification was not statistically significant after this adjustment (p = 0.540). However, given the small BI-RADS 5 subgroup (n = 11), this non-significant result should not be interpreted as evidence of its lack of clinical utility, as the analysis was likely underpowered for this specific variable. Conclusion FNA cytology, when interpreted using the IAC Yokohama System, is a highly accurate and reliable tool for the initial evaluation of BI-RADS 4 and 5 breast lesions. Importantly, our findings demonstrate that older age and larger tumor size are strong, independent predictors of malignancy in this high-risk cohort, highlighting the need to integrate these clinical parameters to optimize risk stratification.